Mechanisms and designs of asymmetrical electrochemical capacitors - Akinwolemiwa, Bamidele; Wei, Chaohui; Chen, George Z. (Elsevier, 2017)
Different charge storage mechanisms in electrochemical energy storage devices are reviewed, including non-Faradaic capacitive, Faradaic capacitive, Faradaic non-capacitive, and their combinations. Specifically, Faradaic capacitive (pseudocapacitive) storage and Faradaic non-capacitive (Nernstian) storage are attributed to the transfer of delocalised and localised valence electrons, respectively. Mathematical and graphical expressions of the respective storage performances are presented. The account is made especially for asymmetrical electrochemical capacitors (AECs), supercapattery and supercabattery. Both hypothetical and experimental examples are presented to demonstrate the merits of supercapattery that combines capacitive and Nernstian electrodes. Enhanced storage performance is shown by properly pairing and balancing the properties of the negatrode (negative electrode) and positrode (positive electrode) in the AEC or supercapattery. In addition, the design, laboratory manufacturing and performance of several stacks of bipolarly connected AEC cells are assessed in terms of commercial feasibility and promise.